Penerapan Analisis SWOT Dalam Menentukan Strategi Pengembangan Sistem Informasi STIKOM Yos Sudarso Purwokerto - Adhi Wibowo; Suyudi Suyudi (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2018)
This research is useful for identifying basic potential information of internal and external factors of strategy determinant that can be used in strategy development. And the results of the analysis describes the related internal business analysis and Information Systems / Information Technology institutions as well as external factors of business and Information Systems / Information Technology institution STIKOM Yos Sudaro Purwokerto. From the analysis result, it is concluded that STIKOM Yos Sudarso Purwokerto need to adopt an aggressive strategy policy in the framework of developing information system to take advantage of the high strength and opportunity in the midst of computer-based college competition in Banyumas Regency.